Cute as candy: a qualitative study of perceptions of snus branding and package design among youth in Norway. Issue 4 (3rd April 2017) - Scheffels, Janne; Lund, Ingeborg
Abstract : Objectives: Snus use has increased among youth in Norway in recent years and is now more prevalent than smoking. Concurrently, a range of new products and package designs have been introduced to the market. The aim of this study was to explore how youth perceive snus branding and package design, and the role, if any, of snus packaging on perceptions of appeal and harm of snus among youth. Participants: Adolescent tobacco users and non-users (N=35) ages 15–17 years. Design: We conducted interviews among 6 focus groups (each with 4–7 participants). Participants were shown snus packages with a variety of designs and with different product qualities (flavour additives, slim, regular, white and brown sachets) and group discussions focused on how they perceived packages and products. The focus group discussions were semistructured using a standard guide, and analysed thematically. Results: The participants in the focus groups narrated distinct images of snus brands and associated user identities. Package design elements such as shapes, colours, images and fonts were described as guiding these perceptions. Packaging elements and flavour additives were associated with perceptions of product harm. The appeal of flavoured snus products and new types of snus sachets seemed to blend in with these processes, reinforcing positive attitudes and contributing to the creation of particular identities for products and their users. Conclusions: The findings indicate that packaging is vital to consumer's identification with, and differentiation between, snus brands. In view of this, snus branding and packaging can be seen as fulfilling a similar promotional role as advertising messages: generating preferences and appeal.